Frederick Jackson Turner and the Westward Expanse: Changing Net Nutrition with Economic Development - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2016)
A population's average stature reflects its cumulative net nutrition and provides important insight when more traditional measures for economic well-being is scarce or unreliable. Heights on the US Central Plains did not experience the antebellum paradox experienced in Eastern urban areas, and statures increased markedly in the late 19th and early 20th centuries. Known for offering migrants economic opportunity, the Central Plains received migrant in-flows from Northern, Southern, and Eastern Europe, and US statures were the tallest in the World. Within the US, individuals from the South were taller than individuals from the North, East, and West. Whites were taller than blacks on the Central Plains where slavery was not the primary labor force, but whites were also taller than blacks in the American South where it was. Immigrants from industrialized Europe were shorter than black and white Americans but taller than Latin Americans and Asians.
Keywords: I10; J11; J71; N31; 330; nineteenth century black and white stature variation; urbanization; US Central Plains